Preventing Foodborne Illness: E. coli “The Big Six” - Susanna Richardson; Renée M. Goodrich-Schneider; Keith R. Schneider (EDIS)
Escherichia coli is a bacterium usually found in the digestive system of healthy humans and animals and transmitted through fecal contamination. There are hundreds of known E. coli strains, with E. coli O157:H7 being the most widely recognized because of the severe illness it causes. In addition to E. coli O157:H7, the U.S. Food and Drug Administration has identified six serogroups (or “strains”), known as the “big six,” which includes E. coli O26, O45, O103, O111, O121, and O145. These are the most commonly seen types of E. coli found in food in the United States that are not O157:H7, and they cause approximately 37,000 cases per year in the United States. This 5-page fact sheet was written by Susanna Richardson, Renée Goodrich Schneider, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, October 2013.